A novel MoNi@Ni(OH)2 heterostructure with Pt-like and stable electrocatalytic activity for the hydrogen evolution reaction. Issue 11 (15th January 2020) - Lu, Xiaoying; Cai, Minmin; Zou, Zehua; Huang, Junfeng; Xu, Cailing
Abstract : A novel Mo0.84 Ni0.16 @Ni(OH)2 heterostructure was successfully fabricated. Abstract : A novel Mo0.84 Ni0.16 @Ni(OH)2 heterostructure was successfully fabricated. Owing to the unique interface structure and strong synergistic effects between different components, the heterostructure shows enhanced activity for the hydrogen evolution reaction (HER), outperforming that of the state-of-the-art Pt/C catalyst.